Definitive or palliative treatment: case report of cancer breast survivor with ovarian mass - Lakhera, Kamal Kishore; Kumar, Naina; Patel, Pinakin; Singh, Suresh; Kumar, Arjun; Singhal , Pranav; Singh Gora, Bhoopendra (International Surgery Journal, 2023)
Cancers survivors with second tumour mass. The difficult thing in these situations is definitive diagnosis. One sentence which shapes the future of a patient-a steep see saw of definitive and palliative treatment. What saves the clinician in this scenario is the immunohistochemistry (IHC). It single handedly brightens the path and leads to conclusion. This case report demonstrated the same in breast cancer survivor.